2013
DOI: 10.1007/s11064-013-1178-x
|View full text |Cite
|
Sign up to set email alerts
|

All-Trans-Retinoic Acid Rescues Neurons After Global Ischemia by Attenuating Neuroinflammatory Reactions

Abstract: Retinoic acid (RA) plays an important role in the developing mammalian nervous system. Based on this concept, some studies have demonstrated the beneficial effects of RA administration on neurogenesis in neuropathological diseases. Some investigations have revealed the anti-inflammatory effects of RA treatment in multiple systems, in addition to its role in neurogenesis. To date, however, the neuroprotective efficacy of RA after cerebral ischemia, especially in the context of its anti-inflammatory effects, has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…However, its effectiveness is limited, and its long‐term benefits are unclear (Wiseman et al , ; Schlitt et al ., ). The unique biological profile of ATRA has attracted considerable interest for many years, and it has been shown to have both neuro and hepatic protective effects (Nagy, ; Kim et al ., ). In the present study it was revealed that ATRA can protect against doxorubicin‐induced cardiotoxicity.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, its effectiveness is limited, and its long‐term benefits are unclear (Wiseman et al , ; Schlitt et al ., ). The unique biological profile of ATRA has attracted considerable interest for many years, and it has been shown to have both neuro and hepatic protective effects (Nagy, ; Kim et al ., ). In the present study it was revealed that ATRA can protect against doxorubicin‐induced cardiotoxicity.…”
Section: Discussionmentioning
confidence: 97%
“…ATRA exhibits not only anticancer effects (Mangiarotti et al ., ; Liu et al ., ; Rosenberg et al ., ; Long et al ., ) but also acts as a new class of cardioprotective agent (Bernard et al ., ; Guleria et al ., ; Kim et al ., ). The results of this study also raise the possibility that ATRA may have therapeutic potential to protect the heart against the toxicity of cancer chemotherapies, suggesting that these compounds, like vincristine (Chatterjee et al ., ), deserve further extensive pharmacology and preclinical investigations.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This observation is in good agreement with the previous study that LPS stimulation attenuates proliferation of OPCs in the amygdala and hippocampus (Wennström et al 2014). This is exemplified by the evidence that stereotactic intracranial injections with LPS increase hippocampal neurogenesis (Kim et al 2013), while systemically administered LPS decreases neurogenesis (Ekdahl et al 2003;Monje et al 2003). Neonatal inflammation influences reactivity to stress, immune regulation, susceptibility to disease, and memory impairment in adulthood (Shanks et al 2000).…”
Section: Suppression Of Opc Proliferation Under Brain Inflammationmentioning
confidence: 98%
“…Neuronal death induced by cerebral ischemia is a major cause of high morbidity and mortality (1). Although previous studies have yielded encouraging results when investigating therapeutic candidates using animal models of cerebral ischemia (2,3), no pharmacological strategies are currently effective in the clinical setting.…”
Section: Introductionmentioning
confidence: 99%